Structural complexity and benthic metabolism: resolving the links between carbon cycling and biodiversity in restored seagrass meadows - T. Kindeberg; K. M. Attard; K. M. Attard; J. Hüller; J. Müller; C. O. Quintana; C. O. Quintana; E. Infantes (Biogeosciences, 2024)
Due to large losses of seagrass meadows worldwide, restoration is proposed as a key strategy for increasing coastal resilience and recovery. The emergence of a seagrass meadow is expected to substantially amplify biodiversity and enhance benthic metabolism by increasing primary productivity and respiration. Nevertheless, open questions remain regarding the metabolic balance of aging seagrass meadows and the roles benthic communities within the seagrass ecosystem play in overall metabolism.